2013
DOI: 10.1007/s13762-013-0418-6
|View full text |Cite
|
Sign up to set email alerts
|

Iron recovery from the waste generated during the cutting of granite

Abstract: Metallic iron is present in the waste left when granite blocks are cut. Thus, the purpose of this study was to characterize this waste using chemical and particle size analyses. To achieve this, X-ray diffraction and scanning electron microscopy coupled with electron back-scattered diffraction were used. To find the method with the best metallic iron recovery from the waste of ornamental rock, three distinct methods were examined: magnetic separation, table concentration and cyclone processing. The first metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…[15] Besides magnetic separation, the thermal reduction process has been investigated for the purpose of recovering iron from residues in studies about reducing pellets made from electric arc furnace dust using natural gas and the investigation of carbothermal reduction of electric arc furnace dust briquettes in a microwave oven. [16,17] In this type of study, which uses fine raw materials, agglomeration processes to produce pellets, sinter, or briquettes are required to avoid clogs in reactors. Among the studies mentioned, there have not been investigations about selfreducing briquettes made from zinc mine tailings, nor any studies proposing a route that combines physical and thermal processes to obtain metallic iron from those tailings.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Besides magnetic separation, the thermal reduction process has been investigated for the purpose of recovering iron from residues in studies about reducing pellets made from electric arc furnace dust using natural gas and the investigation of carbothermal reduction of electric arc furnace dust briquettes in a microwave oven. [16,17] In this type of study, which uses fine raw materials, agglomeration processes to produce pellets, sinter, or briquettes are required to avoid clogs in reactors. Among the studies mentioned, there have not been investigations about selfreducing briquettes made from zinc mine tailings, nor any studies proposing a route that combines physical and thermal processes to obtain metallic iron from those tailings.…”
Section: Introductionmentioning
confidence: 99%
“…Albite and anorthite, were also detected. Such phases have been detected for several researchers in granite waste composition (Li et al, 2013;Junca et al, 2015). Size analysis showed that BOFS is range of 0.479-2187.76 µm, with 90% lesser than 1258.92 µm, and 50% lesser than 478.63 µm.…”
Section: Raw Materials Characterizationmentioning
confidence: 73%
“…These metal particles are widely employed in the automotive and steel industries generating large amounts of wastes with no proper disposal (Nazer et al, 2012). However, the civil industry has been investigating ways to reuse these particulate materials as aggregates for concrete, consequently reducing utilization of natural resources (Junca et al, 2015).…”
Section: Introductionmentioning
confidence: 99%